The stories of jesus a study in the parables. - Danna, Elizabeth ([Place of publication not identified] : Wipf & Stock Publishers, 2016)
The Stories of Jesus is a seven-week Bible study for small groups or individuals. Drawing from history, archaeology, literary studies, and the original languages, this is a one-of-a-kind look at the parables of the Gospels of Matthew, Mark, and Luke. Sitting at the feet of Jesus, the Master Storyteller, you'll gain a fresh appreciation of these familiar stories and be challenged to grow spiritually.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 148.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 600
Keywords: Jesus Christ -- Parables; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books